2002
DOI: 10.1002/1439-7633(20020301)3:2/3<242::aid-cbic242>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Directed Assembly of Bienzymic Complexes from In Vivo Biotinylated NAD(P)H:FMN Oxidoreductase and Luciferase

Abstract: Spatially controlled assembly of enzyme conjugates can be applied to signal amplification systems for biosensors, or synthesis of novel catalysts for enzyme process technology. Artificial bienzymic systems comprised of two enzymes, NAD(P)H‐FMN oxidoreductase and luciferase (represented as blue and orange spheres, respectively, in the schematic representation) were assembled by means of DNA hybridization and streptavidin–biotin interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
146
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(156 citation statements)
references
References 8 publications
(11 reference statements)
3
146
0
7
Order By: Relevance
“…They showed that the use of a simple DNA duplex could enhance the efficiency of many bienzymatic cascades, for example, NAD(P)H:FMN oxidoreductase and luciferase, 45 glucose oxidase (GOx) and horseradish peroxidase (HRP), 46 and two subdomains of cytochrome P450 BM3 in a cascade. 47 Because DNA duplexes can only regulate the distance between adjacent enzymes, high-order 2D and 3D DNA nanostructures can exert more precise control on multienzymatic cascades because of their abilities to regulate not only the distance but also other parameters, such as the arrangement and the concentration.…”
Section: Regulating Reaction Pathways For Bioinspired Nanofactoriesmentioning
confidence: 99%
“…They showed that the use of a simple DNA duplex could enhance the efficiency of many bienzymatic cascades, for example, NAD(P)H:FMN oxidoreductase and luciferase, 45 glucose oxidase (GOx) and horseradish peroxidase (HRP), 46 and two subdomains of cytochrome P450 BM3 in a cascade. 47 Because DNA duplexes can only regulate the distance between adjacent enzymes, high-order 2D and 3D DNA nanostructures can exert more precise control on multienzymatic cascades because of their abilities to regulate not only the distance but also other parameters, such as the arrangement and the concentration.…”
Section: Regulating Reaction Pathways For Bioinspired Nanofactoriesmentioning
confidence: 99%
“…27 Niemeyer et al reported multienzyme colocalization using DNA hybridization catalyzed cascaded reactions on planar surfaces, resulting in enhanced enzymatic activity. 20 Likewise, Muller and Niemeyer employed protein engineering combined with DNA-hybridization-directed evolution to develop supramolecular complexes using DNA as a scaffold for enzyme assembly. 21 They attached multiple enzymes by covalent binding to short single-stranded biotinylated and thiolated DNA oligonucleotides and brought them together using DNA-directed hybridization of short DNA with long complementary capture DNA to form a scaffold.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This approach can be used, for instance, to generate multienzyme constructs as model systems for the investigation of "substratechanneling" processes. (12) On the other hand, the DNA-protein conjugates can be used to translate DNA arrays on surfaces into protein arrays (left part of Fig. 1).…”
Section: Introductionmentioning
confidence: 99%